BREEDING CERTAIN TRAITS OF THE SNAKE CUCUMBER (CUCUMIS MELO VAR. FLEXUOSUS) THROUGH HONEYCOMB SELECTION - F. N. M. Al-Khazarji; M. M. M. Alabdaly (مجلة الأنبار للعلوم الزراعية)
at the Abu Ghraib Research Station during fall of 2022 and 2023 and spring 2023 and 2024. It involved three cycles of the honeycomb selection method and three snake cucumber genotypes. The plants from the second selection cycle significantly outperformed the others in all traits. The results showed that the second genotype (V2) significantly outperformed the others in all traits providing the highest values for leaf area (222.24 dm²), sex ratio (14.14%), and main branches plant-1 (4.71 branches plant-1) compared to the lowest for the V3 genotype at 139.44 dm², 8.84%, and 3.00 branches plant-1, respectively. The interaction between the study's two factors had a significant effect, with the second genotype plants in the second selection cycle achieving the highest values for all traits, compared to the lowest for the original plants of the third genotype. The narrow-sense heritability values for the two selection criteria in the second selection cycle were 40.67% and 39.14% for branch numbers and sex ratio, respectively, confirming the high yield efficiency of these two criteria. Selection led to increased homogeneity of the plants for several traits, as indicated by an increase in the mean and a decrease in the standard deviation and coefficient of variation as the selection cycles progressed